Analisis Pertumbuhan Ekonomi Jawa Timur Pada Masa Covid-19 - Putri, Elma Agistiana; Rizal, Fitra (CV. Civiliza Publishing, 2022)
This study aims to analyze economic growth during the Covid-19 period in East Java for the 2019-2021 period. This study used a qualitative method using a library research approach. Based on the results of the study, economic growth during the Covid-19 period in East Java for the 2019-2021 period experienced a drastic decline. Where in quarter IV-2020 against quarter IV-2019 (y-on-y) East Java's economy contracted by 2.64 percent. In the first quarter of 2020, growth began to slow down to 2.97 percent. Furthermore, in the second quarter of 2020 it contracted to 5.98 percent compared to the second quarter of 2019. And in the second quarter of 2021 economic conditions began to improve even though they were still contracting, namely by 7.05 percent. Penelitian ini bertujuan untuk menganalisis pertumbuhan ekonomi pada masa Covid-19 di Jawa Timur periode 2019-2021. Penelitian ini menggunakan metode kualitatif dengan menggunakan pendekatan studi Pustaka (Library Research). Bedasarkan hasil penelitian menunjukkan pertumbuhan ekonomi pada masa Covid-19 di Jawa Timur periode 2019-2021 mengalami penurunan secara drastis. Dimana pada triwulan IV-2020 terhadap triwulan IV-2019 (y-on-y) ekonomi Jawa Timur terkontraksi sebesar 2,64 persen. Pada triwulan I-2020, pertumbuhan mulai melambat menjadi 2,97 persen. Selanjutnya triwulan II-2020 terkontraksi mencapai 5,98 persen dibanding triwulan II-2019. Dan pada Triwulan II-2021 kondisi ekonomi mulai membaik walaupun masih terkontraksi, yaitu sebesar 7,05 persen.